Ammonia-sensitive fibre optic probe utilising an immobilised spectrophotometric indicator - Çag?lar, Perihan; Narayanaswamy, Ramaier (My University, 1987)
The immobilisation of an indicator dye reagent for the development of fibre optic probes for detecting ammonia vapour has been investigated. The indicator dye reagent bromothymol blue was immobilised on a hydrophilic polymer matrix and the concentration of ammonia in the vapour phase determined in the range 1.5 × 10-3-60 × 10-3 mol l-1 by reflectance measurements. Some possible interferences from other vapours were also investigated.
Keywords: Ammonia sensor; Ammonia-sensitive probe; Fibre optic probe; Optical fibre; Spectrophotometry